2018
DOI: 10.1016/j.scitotenv.2017.09.266
|View full text |Cite
|
Sign up to set email alerts
|

Short-term effects of fine particulate matter on acute myocardial infraction mortality and years of life lost: A time series study in Hong Kong

Abstract: Previous studies have applied years of life lost (YLL) as a complementary indicator to assess the short-term effect of the air pollution on the health burden from all-cause mortality, but sparsely focused on individual diseases such as acute myocardial infraction (AMI). In this study, we aimed to conduct a time-series analysis to evaluate short-term effects of fine particulate matter (PM) on mortality and YLL from AMI in Hong Kong from 2011 to 2015, and explore the potential effect modifiers including sex and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(21 citation statements)
references
References 47 publications
0
21
0
Order By: Relevance
“…We studied the elderly and the elderly make up a high-risk group[22,23]. The short-term association of PM 2.5 with mortality from circulatory diseases was consistent with previous epidemiological studies[17]. PM 2.5 may reduce cardiac parasympathetic input leading to decreased heart rate variability (HRV)[24,25].…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…We studied the elderly and the elderly make up a high-risk group[22,23]. The short-term association of PM 2.5 with mortality from circulatory diseases was consistent with previous epidemiological studies[17]. PM 2.5 may reduce cardiac parasympathetic input leading to decreased heart rate variability (HRV)[24,25].…”
Section: Discussionmentioning
confidence: 55%
“…No study on the relationship between short-term exposure to PM 2.5 and mortality risk has been conducted in Changchun. Since the elderly are more vulnerable to air pollution[17,18], we therefore conducted a time-series study of the elderly in Changchun to evaluate the short-term effect of PM 2.5 on non-accidental and circulatory disease mortality, and explored the potential effect modification by sex, education and death location.…”
Section: Introductionmentioning
confidence: 99%
“…Several reviews of the adverse health effects of air pollution in the Chinese population yield similar results (Lu et al 2015 ; Shang et al 2013 ). In China, the short-term effect of the air pollution on the health burden has been studied in several cities such as Beijing, Shanghai, Wuhan, and Shenzhen (Lai and Brimblecombe 2017 ; Li et al 2015 ; Liang et al 2017 ; Lin et al 2017 ; Zhang et al 2017 ). A systematic review of 33 time series and case-crossover studies provided additional insights into the heterogeneity in effects on daily mortality after exposure to air pollution in China (Shang et al 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…About 80% of those deaths are due to heart diseases and stroke 1 . Epidemiological and experimental studies have also demonstrated the causal relationship between acute PM 2.5 exposure and elevated morbidity and mortality of cardiovascular diseases 25 . Many researches have been done targeting the association between PM 2.5 and cardiovascular diseases, however, the underlying mechanism is still poorly understood.…”
Section: Introductionmentioning
confidence: 99%